Training medical students in health promotion: twenty years of experience at the Faculty of Medicine of the University of Geneva - Thomas Mattig; Philippe Chastonay; Emmanuel Kabengele; Laurent Bernheim (Tabriz University of Medical Sciences, 2017)
Background: In most cases, the work of medical doctors, be they general practitioners or specialists, involves some dimension of health promotion (HP). There is thus ample justification for increasing the awareness of medical students vis-à-vis HP and its relevance for their future practice.Methods: In the context of a major curriculum reform (problem-based learning [PBL]) at the Faculty of Medicine of the University of Geneva in the mid-1990s, several steps were taken to strengthen HP throughout the curriculum and include HP in its key domains as defined by the Ottawa Charter (OC).Results: First, the political dimension of HP was developed in a series of first- and fifth-year lectures and third-year workshops; second, community action was strengthened through a third year one-month community immersion program; third, the development of personal skills was integrated into second- and third-year PBL cases and into fourth-and fifth-year learning activities in clinical settings as well as second- and third-year HP electives; in terms of reorienting health services, the chosen approach included the development of a HP-specific track in the context of a Certificate of Advanced Studies (CAS) in Community Health and a Master of Advanced Studies(MAS) in Public Health. Furthermore, a supportive intra-university environment was created through a collaborative convention with Health Promotion Switzerland, which is in charge of coordinating HP in Switzerland.Conclusion: In our view, HP teaching for medical students seems all the more relevant given that future medical doctors will have to take care of an increasing number of patients likely to develop chronic non-communicable diseases.